Four methodological specifications to identify territory aptitude (2010)
This article reviews four conditions that orientate methodologically the studies of territory aptitude. The conditions derive the response depending on the foreseen interventions and the place where they have to be carried out: one is obtained from the instruments of soil evaluation; another with the methodologies of assignment – location-, one more has developed tools that confirm several productive alternatives with its requirements of operation faced to the capacities of the area and the last one is oriented to project formulation.